A representação do movimento no português paulista - Verena Kewitz (Filologia e Linguística Portuguesa, 2013)
The aim of this article is to analyze how motion can be organized and represented in Paulista Portuguese (Portuguese spoken in São Paulo), in data taken from several genres of text from the 18th to the 20th centuries. I take into account the patterns proposed by Talmy (2000b), and the representation of path points in motion events. The analysis is qualitative and quantitative, taking into account the discursive properties of the texts in the corpora, based on the Discourse Traditions model.